Міссісіпі - маловідома північноамериканська цивілізація доколумбової епохи - Балушок, В. (Народна творчість та етнографія, 2005)
The article is devoted to the culture of Mississippi that existed on the Southern-East of the USA in 8th-16th cc. and is considered to be the most developed in the pre-Columbian period. It's distinctive features are: big city centers, property and social stratification, powerful rulers and well-developed network of temples with numerous priest and human sacrifices. All these features give the right to classify the society of Mississippians to early-state civilization or proto-civilization.